Plant odor and sex pheromone are integral elements of specific mate recognition in an insect herbivore. (27th August 2018) - Borrero‐Echeverry, Felipe; Bengtsson, Marie; Nakamuta, Kiyoshi; Witzgall, Peter
Abstract: Specific mate recognition relies on the chemical senses in most animals, and especially in nocturnal insects. Two signal types mediate premating olfactory communication in terrestrial habitats: sex pheromones, which blend into an atmosphere of plant odorants. We show that host plant volatiles affect the perception of sex pheromone in males of the African cotton leafworm Spodoptera littoralis and that pheromone and plant volatiles are not perceived as independent messages. In clean air, S . littoralis males are attracted to single synthetic pheromone components or even the pheromone of a sibling species, oriental cotton leafworm S . litura . Presence of host plant volatiles, however, reduces the male response to deficient or heterospecific pheromone signals. That plant cues enhance discrimination of sex pheromone quality confirms the idea that specific mate recognition in noctuid moths has evolved in concert with adaptation to host plants. Shifts in either female host preference or sex pheromone biosynthesis give rise to new communication channels that have the potential to initiate or contribute to reproductive isolation.